Gingival crevicular fluid levels of RANKL and OPG in periodontal diseases: implications of their relative ratio - Nagihan Bostanci (Blackwell Synergy, 2007)
Aim: Receptor activator of NF-kB ligand (RANKL) and osteoprotegerin (OPG) are a system of molecules that regulate bone resorption. This study aims to compare the levels of RANKL, OPG and their relative ratio in gingival crevicular fluid (GCF) of healthy and periodontal disease subjects. Material and Methods: GCF was obtained from healthy (n521), gingivitis (n522), chronic periodontitis (n528), generalized aggressive periodontitis (n525) and chronic periodontitis subjects under immunosuppressant therapy (n511). RANKL and OPG concentrations in GCF were measured by enzyme-linked immunosorbent assays. Results: RANKL levels were low in health and gingivitis groups, but increased in all three forms of periodontitis. OPG levels were higher in health than all three periodontitis, or gingivitis groups. There were no differences in RANKL and OPG levels between chronic and generalized aggressive periodontitis groups, whereas these were lower in the immunosuppressed chronic periodontitis group. The RANKL/ OPG ratio was significantly elevated in all three periodontitis forms, compared with health or gingivitis, and positively correlated to probing pocket depth and clinical attachment level. Conclusion: GCF RANKL and OPG levels were oppositely regulated in periodontitis, but not gingivitis, resulting in an enhanced RANKL/OPG ratio. This ratio was similar in all three periodontitis groups and may therefore predict disease occurrence.